1998
DOI: 10.1007/s002140050309
|View full text |Cite
|
Sign up to set email alerts
|

The singlet and triplet states of phenyl cation. A hybrid approach for locating minimum energy crossing points between non-interacting potential energy surfaces

Abstract: The phenyl cation is known to have two lowenergy minima, corresponding to 1 A 1 and 3 B 1 states, the ®rst of which is more stable by ca. 25 kcal/mol. The minimum energy crossing point between these two surfaces, located at various levels including a hybrid method ®rst described here, lies just above the minimum of the triplet, 0.12 kcal/mol at the CCSD(T)/cc-pVDZ// B3LYP/SV level, and there is signi®cant spin-orbit coupling between the surfaces at this point. On the basis of these results, the lifetime of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
594
0
14

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 841 publications
(614 citation statements)
references
References 13 publications
6
594
0
14
Order By: Relevance
“…For the distal oxygen atom attack, the barrier height is computed to be 91.7 kJ mol À1 ( 5 I d -ts1) at the quintet surface while the barrier height in the triplet surface is computed to be twice as much (Figure 1). This difference demands a spin inversion [15] and suggests that the antiferromagnetic exchange observed for this species hinders its reactivity. The optimized structure of 5 I d -ts1 along with the computed spin density plot is shown in Figure 2.…”
Section: Fementioning
confidence: 96%
“…For the distal oxygen atom attack, the barrier height is computed to be 91.7 kJ mol À1 ( 5 I d -ts1) at the quintet surface while the barrier height in the triplet surface is computed to be twice as much (Figure 1). This difference demands a spin inversion [15] and suggests that the antiferromagnetic exchange observed for this species hinders its reactivity. The optimized structure of 5 I d -ts1 along with the computed spin density plot is shown in Figure 2.…”
Section: Fementioning
confidence: 96%
“…In particular, the nature of the ground state multiplicity for the parent and substituted phenyl cations has attracted considerable attention. The parent system is known to have two low-energy minima which corresponds to the 1 A 1 and 3 B 1 states, with the intersection between the lowest energy singlet and triplet hypersurfaces lying close to the triplet geometry and energy [7]. Coupled with nontrivial spin-orbit coupling between these two states near the crossing point [8], the triplet phenyl cation is a shortlived intermediate that rapidly decays [7] to the ground singlet state 102 kJ/mol below the triplet minimum [9].…”
Section: Introductionmentioning
confidence: 99%
“…The parent system is known to have two low-energy minima which corresponds to the 1 A 1 and 3 B 1 states, with the intersection between the lowest energy singlet and triplet hypersurfaces lying close to the triplet geometry and energy [7]. Coupled with nontrivial spin-orbit coupling between these two states near the crossing point [8], the triplet phenyl cation is a shortlived intermediate that rapidly decays [7] to the ground singlet state 102 kJ/mol below the triplet minimum [9]. The phenyl cation has been isolated and characterized in argon [10,11] and LiCl matrices [12] and in the gas phase [13], and indirectly detected in aqueous solution with a lifetime of <500 ps [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus it was found that in the case of phenyl cation the singlet-triplet splitting is relatively small and with a right choice of substituents at the phenyl ring can even be reversed [19]. The geometry for the cross-point between singlet and triplet has been calculated as well as spin orbit coupling for this transient structure [20]. Other reactive intermediates that were extensively studied by Squires and coworkers are o-, m-, and p-isomeric benzyne anions [21][22][23].…”
mentioning
confidence: 99%